Tissue engineering intervertebral disc and preparation method and application thereof
Patent Information
- Application Number
- CN202411392448.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has insufficient biocompatibility and mechanical properties of materials in spinal fusion surgery, resulting in unsatisfactory disc repair results, especially when simulating the stress of humans walking upright spine.
The tissue that uses the nucleus pulposus composed of GelMA, PEGDA, photoinitiator and L-cysteine to the fibrous annular fibrillar composed of poly(D,L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen The engineered intervertebral disc is prepared by ultraviolet curing and electrospinning to improve the elasticity and axial compression resistance of the material.
This material promotes cell proliferation in vitro, and in vivo implantation can effectively repair disc degeneration, reduce the loss of disc signal strength, and has good biocompatibility and mechanical properties. It is suitable for preclinical research and spinal repair.
Smart Images

Figure BDA0005072804550000061 
Figure BDA0005072804550000071 
Figure BDA0005072804550000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of tissue engineering, and specifically relates to a tissue engineering intervertebral disc and a preparation method and application thereof. Background Art
[0002] Spinal degeneration is closely related to age. Congenital development, nature of work, labor intensity and especially trauma are all predisposing factors. With age, cervical bone hyperplasia, disc degeneration and ligament calcification occur more frequently. Acute injury and chronic strain of the spine can lead to premature or accelerated local degeneration. Spinal fusion is an effective surgical method for when spinal stability is destroyed or correction is required. It is currently used for a small number of functional disorders caused by disc herniation or spinal stenosis without spondylolisthesis. The fusion technique causes the original active segments of the spine to lose function and form a whole, which requires internal fixation.
[0003] Most implants in early spinal fusion were pedicle screws and intervertebral fusion cages. Bone defects, bone tumor resection and infection after spinal fusion and injury require implant repair. Ando et al. prepared a rabbit posterolateral lumbar fusion and tibial intramedullary model and found that there was obvious new bone formation on the most prominent vertebral plate at the edge of the implanted SPG-178 composite material. Deng Biquan et al. removed the nucleus pulposus of the L4 / 5 intervertebral disc of the rabbit and implanted silk fibroin / nanohydroxyapatite composite materials to reconstruct the spinal segment. They found that the composite material was partially degraded, fibrous tissue was visible around it, new woven bone was present inside, and crypt cells and osteocytes were scattered, indicating that the material has good biocompatibility and mechanical properties.
[0004] Gel was once used to repair damaged annulus fibrosus, but its mechanical properties are limited, and the repair effect is not ideal when used alone. Lee et al. used the bone-promoting growth factor BMP-2, and the amphiphilic peptide nanofibers formed by self-assembly can display bioactive signals on their surface to create a gel scaffold for osteogenesis for regenerative medicine research. Currently, the FDA has approved the use of recombinant BMP-2 in anterior spinal fusion surgery. The problem of recombinant human bone morphogenetic protein 2 (rhBMP-2) accompanied by inflammatory response in spinal fusion is also worthy of attention. Sharifi et al. prepared scaffolds using copper ion-containing nanofibers and gelatin / collagen by freeze-drying, and studied the growth and activity of stem cell-derived osteoblasts. Cell biocompatibility experiments showed that the scaffold had more activity and osteoblast growth, and was a scaffold suitable for bone tissue engineering.
[0005] The intervertebral disc consists of two parts: the annulus fibrosus located in the peripheral part and the nucleus pulposus located in the central part. The main structure of the annulus fibrosus is composed of multiple layers of staggered fibrocartilage rings, which can firmly connect the vertebral bodies and have a certain degree of elasticity and toughness. In addition to bearing pressure, it can also prevent the nucleus pulposus from overflowing. The nucleus pulposus is a white gelatinous substance with high elasticity. When the nucleus pulposus is affected by gravity, it expands in all directions and squeezes the annulus fibrosus to extend and expand around. As early as 2006, Mizuno et al. established a composite tissue-engineered intervertebral disc, which was cylindrical and consisted of a sodium alginate gel nucleus pulposus and an outer shell composed of annulus fibrosus. Histomorphological observations found that there were obvious morphological differences in the tissue formation of the annulus fibrosus and nucleus pulposus cell implantation areas; biochemical analysis showed that the content of DNA, proteolytic enzymes and collagen in tissue-engineered intervertebral discs increased with time.
[0006] Nanoscale materials have broad application prospects for spinal fusion. With the continuous development of materials science, quite a number of scaffold materials with good performance have been discovered. For example, Li et al. prepared ideal zein / L-polylactic acid nanofibers by coaxial electrospinning and combined them with bone morphogenetic protein 2 (BMP-2) and dexamethasone (DEX) for biphasic controlled release in bone tissue engineering. However, most in vivo experiments are based on animal models, and there is still a certain gap in simulating the stress of the human spine during upright walking. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a tissue engineering intervertebral disc, which is composed of a nucleus pulposus and an annulus fibrosus.
[0008] Furthermore, the nucleus pulposus components include GelMA, PEGDA, a photoinitiator and L-cysteine; the photoinitiator is I-2959 or LAP.
[0009] Furthermore, the mass ratio of the GelMA, PEGDA, photoinitiator and L-cysteine is 1-2:1-2:0.5:0-1.
[0010] Furthermore, the annulus fibrosus components include poly (D, L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen.
[0011] Furthermore, the fiber ring is composed of poly (D, L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen in a mass ratio of 0-10:0-10:0-1.
[0012] The present invention also provides a method for preparing the tissue engineering intervertebral disc, wherein the nucleus pulposus is made by ultraviolet light curing, and the annulus fibrosus is made by electrostatic spinning.
[0013] Furthermore, the UV curing is to prepare GelMA, PEGDA and I-2959 into an aqueous solution in a mass percentage of 5:5:0.5, and irradiate the aqueous solution under a 365nm LED UV curing lamp for 2 hours.
[0014] Furthermore, the electrospinning method is to prepare a precursor HFIP spinning solution by configuring poly (D, L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen in a mass percentage of 3:6:1, and use a portable electrospinning apparatus for spinning.
[0015] The present invention also provides the use of the tissue engineered intervertebral disc in preparing a product for repairing intervertebral disc degeneration and reducing the loss of intervertebral disc signal intensity.
[0016] The present invention has the following beneficial effects:
[0017] The material provided by the present invention has good elasticity and axial compression resistance, can promote in vitro cell proliferation, enhance cell viability, and can effectively repair intervertebral disc degeneration and reduce the loss of intervertebral disc signal intensity when implanted in vivo. This material can better serve preclinical research. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 Appearance morphology of hydrogels in each group (a: G1, b: G2, c: G3, d: G4, e: G5, f: G0);
[0020] Figure 2 SEM of hydrogels in each group (a: G1, b: G2, c: G3, d: G4, e: G5, f: G0);
[0021] Figure 3 Swelling properties of hydrogels in each group;
[0022] Figure 4 Infrared spectra of each group;
[0023] Figure 5 XRD patterns of each group;
[0024] Figure 6 SEM images of the degradation of each group of hydrogels at different time periods (2w period a: G1, b: G2, c: G3, d: G4, e: G5, f: G0; 4w period g: G1, h: G2, i: G3, j: G4, k: G5, l: G0);
[0025] Figure 7 Degradation rate of hydrogels in each group at different periods;
[0026] Figure 8 Morphology of fiber membranes collected at different linear speeds (a: 8 m / s, b: 10 m / s, c: 13 m / s, d: 15 m / s);
[0027] Fig. 9 SEM of fiber membranes in each group (a: P1, b: P2, c: P3, d: P4, e: P5, f: P0);
[0028] Fig.10 Infrared spectra of each group;
[0029] Fig.11 Contact angle results of each group;
[0030] Fig.12 SEM images of the degradation of each group of membranes at different time periods (a: P1, b: P2, c: P3, d: P4, e: P5, f: P0 for the 2-week period; g: P1, h: P2, i: P3, j: P4, k: P5, l: P0 for the 4-week period);
[0031] Fig.13 Degradation rate of each group of membranes at different periods
[0032] Fig.14 Laser confocal microscopy images of hydrogels in each group (a: G1, b: G2, c: G3, d: G4, e: G5, f: G0);
[0033] Fig.15 Laser confocal microscopy images of fiber membranes in each group (a: P1, b: P2, c: P3, d: P4, e: P5, f: P0);
[0034] Fig.16 Cell viability of each group at different periods (a. hydrogel; b. membrane);
[0035] Fig.17 Flowchart of tissue engineered intervertebral disc construction;
[0036] Fig.18 a. Stress-strain curve and b. elastic modulus diagram of the test group;
[0037] Fig.19 ae. stress-strain curves and f. elastic modulus diagrams of experimental groups;
[0038] Fig. 20Physical and in vivo imaging examination of tissue engineered intervertebral disc (TE-IVD) (immediate postoperative periods d, f, h, j; 4 weeks postoperative period: e, g, i, k; Control group: dh, ei are the same rat; TE-IVD group: fj, gk are the same rat);
[0039] Fig.21 HE and MASSON staining were performed in each group. DETAILED DESCRIPTION
[0040] Now, various exemplary embodiments of the present invention are described in detail. The methods in the examples are conventional methods unless otherwise specified, and the reagents used are conventional commercially available reagents or reagents prepared by conventional methods unless otherwise specified. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] Materials and instruments
[0046] The experimental materials are shown in Table 1.
[0047] Table 1 Experimental materials details
[0048]
[0049]
[0050]
[0051] The experimental instruments are shown in Table 2.
[0052] Table 2 Experimental instrument details
[0053]
[0054] Example 1 Preparation and characterization of GelMA / PEGDA hydrogel 1.1 Grouping
[0055] The photosensitive gel raw material (GelMA / PEGDA), photoinitiator (I-2959 / LAP), and functional material (L-cysteine) were divided into six groups according to the following proportions, as shown in Table 3.
[0056] Table 3 Hydrogel grouping (%, W / W)
[0057]
[0058] 1.2 Preparation method
[0059] According to the corresponding components in Table 3, a precursor PBS solution was prepared. Under light-proof conditions, the solution was stirred magnetically in a 40°C water bath for 8 h to fully dissolve. Then, ultrasonic dispersion was performed for 20 min. After standing for 10 min, the remaining bubbles were removed. The solution was then poured into a 12-well plate and irradiated under a 365nm LED UV curing lamp for 2 h to obtain a GelMA / PEGDA hydrogel.
[0060] 1.3 Appearance
[0061] The appearance of the hydrogel is Figure 1 As shown in the figure, the texture of each group after gelation is soft and has a certain elasticity. The gels of groups G1-G5 are slightly yellow and translucent, while the gel of group G0 is pure white and opaque.
[0062] 1.4 Microstructure under scanning electron microscope
[0063] The GelMA and composite gels were observed by SEM under UV illumination. Figure 2As shown, it can be found that the G1-G5 groups have a porous structure inside, and the pore size distribution is irregular. Compared with G4 and G5, the pore wall distribution of G1-3 is regular and dense. Such a structure is conducive to the storage and transportation of nutrients, and can also provide space for cell growth. With the addition of cysteine, the G4 group can achieve cross-linking through the thiol-ene reaction in the "click" reaction, cross-linking the thiol group of the cysteine side chain with the macromolecule containing double bonds to form a hydrogel. This cross-linked "protein-polymer hybrid hydrogel" will change the conformation of the original polymer hydrogel ( Figure 2 Middle d: the pore wall is more rounded and smooth), thus changing the properties of the hydrogel. In addition, G0 under electron microscopy did not show an obvious porous structure ( Figure 2 (f)
[0064] 1.5 Swelling properties
[0065] Swelling rate: The hydrogel was immersed in PBS at 37°C for 24 h, and its swelling weight W s Then, the hydrogel was frozen at -20 °C overnight and freeze-dried using a vacuum freeze dryer to remove water to obtain the dry weight W d The calculation formula of the hydrogel expansion rate is as follows:
[0066] Expansion rate (%) = (W s -W d ) / W s ×100 (1)
[0067] The equilibrium swelling ratio is calculated as follows:
[0068] Equilibrium swelling ratio = W s / W d (2)
[0069] W in formulas (1) and (2) s W is the weight of the gel at swelling equilibrium; d is the weight of the dry gel at swelling equilibrium.
[0070] The expansion rate of each group is Figure 3 As shown in a, G186.48965±0.59814%, G281.83027±5.5383%, G385.54095±0.60288%, G489.29204±0.21951%, G579.03513±0.24983%, G086.78694±0.40869%. Among them, G4 had the largest expansion rate, and G5 had the smallest expansion rate. The P value between the groups was <0.01, which was significantly different. Figure 3Middle b shows the equilibrium swelling ratios of each group: G17.41118±0.32005, G25.94081±2.15783, G36.9241±0.28869, G49.34148±0.19267, G54.77033±0.05682, G07.57308±0.23347. Among them, G4 had the largest equilibrium swelling ratio, and G5 had the smallest equilibrium swelling ratio. The P value between the groups was <0.01, which was significantly different.
[0071] 1.6 Infrared spectroscopy
[0072] The functional groups of the samples were investigated by Fourier transform infrared spectroscopy. Figure 4 It can be seen that each group has a strong CH stretching peak of the -CH3 group (2866cm -1 , where G1-5 components are listed as 2 peaks); G1-5 groups have two olefin C=C double bond strong stretching vibration peaks (1635cm -1 , 1523cm -1 ); The G0 group has two very strong C=O stretching vibration peaks (1725cm -1 , 1092cm -1 ).
[0073] 1.7XRD
[0074] The freeze-dried aerogel powder was analyzed by X-ray diffraction analysis (XRD, Smart Lab 3KW, Rigaku, Japan) to determine the material type. The diffractometer line source uses a Cu target, the maximum tube voltage is 60kV, the maximum tube current is 60mA, and the scanning speed is 6° / min. The test data is processed using MDI Jade6 software and compared with the diffraction peak position of the standard PDF card to analyze which phases the sample to be tested is composed of.
[0075] Figure 5 As shown in the figure, compared with the standard PDF card of C (PDF#26-1076), the strong peak at 26° is offset, and each group moves to the low angle (20°) indicated by the arrow. This phenomenon represents the expansion of the interlayer spacing, indicating that the substance is a composite substance, which may be related to the use of a photoinitiator. The XRD analysis of each group shows that there is a diffraction peak at 2θ=20°, reflecting the (006) crystal plane of C. In addition, the peaks of groups G2 and G3 are sharper, indicating that the crystal quality is high, that is, the arrangement of C atoms in the crystal is more orderly, and there are no or few structural defects or impurities. The peaks of the other four groups are not sharp enough or there is a broadening phenomenon, which may mean that the crystal has defects or an incomplete structure or that the crystal has impurities or is amorphous.
[0076] 1.8 In vitro degradation
[0077] The samples were cut into cylinders with a height of 2 cm and a diameter of 1.5 cm. After freeze-drying and weighing, they were immersed in a PBS solution at a constant temperature of 37°C and stored in a constant temperature shaking box. The samples to be tested were taken out at 2 weeks and 4 weeks, and the degradation characteristics were analyzed by measuring the mass loss of the dried samples after degradation.
[0078] Degradation rate (%) = (W0-W t ) / W0×100 (3)
[0079] W in formula (3) t is the dry weight of the hydrogel at different times, and W0 is the dry weight before the degradation experiment.
[0080] Photocurable biohydrogel has good formability and biocompatibility. Hydrogel has different polymerization characteristics from traditional polymers. The degradation mechanism of hydrogel is attributed to the breakage of polymer molecular chain. Its degradation pathway is mainly hydrolysis (such as synthetic hydrogel PEG, PLA, etc.), enzymatic hydrolysis (such as collagen, gelatin, hyaluronic acid) and dissolution (such as ion-crosslinked sodium alginate hydrogel). According to the degradation mechanism of different hydrogels, a hydrogel of a certain shape is placed in an in vitro water environment or an in vivo environment. After a certain period of time, the mass change before and after degradation is calculated and compared. The degradation rate or degradation percentage of the hydrogel can be obtained by dry weighing method. In the research results of the present invention, each group showed different degrees of degradation. At 4w, the degradation rate of G2 group was higher, while the degradation rate of G3 and G0 groups was relatively low. *P=0.01317 between G2 and G0 groups, **P=0.043 between G3 and G0 groups, all less than 0.05, indicating that with the addition of PEGDA, the degradation time can be extended.
[0081] Example 2 Preparation and characterization of electrospun PLGA / PCL fiber membrane
[0082] 2.1 Grouping
[0083] The high molecular weight polymer (PLGA / PCL) and functional material (type I collagen) were divided into six groups according to the following proportions, as shown in Table 4.
[0084] Table 4 Electrospun membrane grouping (%, W / W)
[0085]
[0086] 2.2 Electrospinning parameters
[0087] According to the corresponding components in Table 4, the precursor HFIP spinning solution was prepared. Then ultrasonic dispersion was performed for 20 minutes to remove the residual bubbles. After standing for 10 minutes, the solution was sucked into a 5 mL syringe. The ambient temperature was 25°C and the humidity was 45%. The spinning was performed using a portable electrospinning apparatus. The electrospinning parameters were as follows: propulsion speed 1 mL / h; output voltage 15 kV; needle 22 G; needle distance to the collection device (drum) 15 cm.
[0088] 2.3 Preparation of electrospun ordered fibers
[0089] In order to obtain ordered fibers, it is necessary to maintain the roller at a certain linear speed. Referring to the linear speed settings of the electrospinning ordered fiber roller reported in different literatures, the present invention first selected four linear speeds of 8m / s, 10m / s, 13m / s, and 15m / s to collect the P0 group fiber membranes. The results are as follows: Figure 8 As shown. Figure 8 Figures a and b show that the relatively low linear velocity makes the fiber membrane tend to be disorderly distributed. Figure 8 Figures c and d show that a relatively high linear speed is more conducive to the preparation of ordered fibers. However, a higher rotation speed will disturb the airflow, throw out the electrospinning jet, and make it difficult to deposit on the drum. Therefore, the subsequent groups of fiber membranes of the present invention were collected at a linear speed of 13 m / s.
[0090] 2.4 Micromorphology
[0091] The microstructures of the six nanofiber membranes were observed by SEM. Fig. 9 The results show that the prepared fiber membranes are all nanometer-sized and roughly arranged in order. The average diameters of the fibers in each group are: P1 0.14μm, P2 0.20μm, P3 0.20μm, P4 0.27μm, P5 0.22μm, P0 0.28μm.
[0092] It is suggested that the diameter of the composite fiber increases slightly with the addition of PCL, and the composite fiber has a relatively smaller fiber diameter than pure PCL fiber.
[0093] 2.5 Infrared spectroscopy
[0094] The functional groups of the samples were investigated by Fourier transform infrared spectroscopy. Fig.10 It can be seen that each group has a strong CH stretching peak of the -CH3 group (2950cm -1 , divided into 2 to 3 peaks); each group has a strong C=O stretching vibration peak (1730cm -1 ); P1-5 groups all have a strong COC stretching vibration peak (1166cm -1 ), 1 CO strong stretching vibration peak (1086cm -1 ).
[0095] 2.6 Water contact angle
[0096] The contact angle (WCA) was measured at 24°C. Fig.11 As shown in the figure, the water contact angles of each group are greater than 90°, which are hydrophobic materials. Among them, the P1 group is 116.61±2.72°, the P2 group is 113.51±2.26°, the P3 group is 108.32±6.91°, the P4 group is 98.10±15.63°, the P5 group is 102.07±1.78°, and the P0 group is 124.70±3.52°. The pure PLGA and PCL membranes have high hydrophobicity. With the addition of natural material type I collagen, the hydrophobicity of the fiber membrane tends to decrease.
[0097] 2.7 In vitro degradation
[0098] The samples were cut into 1cm×1cm squares, freeze-dried and weighed, then immersed in a PBS solution at a constant temperature of 37°C and stored in a constant temperature shaking box. The samples to be tested were taken out at 2 weeks and 4 weeks, and the degradation characteristics were analyzed by measuring the mass loss of the dried samples after degradation.
[0099] Degradation rate (%) = (W0-W t ) / W0×100(3)
[0100] W in formula (3) t is the dry weight of the fiber membrane at different times, and W0 is the dry weight before the degradation experiment.
[0101] As the degradation time increases, the surface roughness of the polymer film increases, the fibers curl, entangle and fuse together, the distribution tends to be disordered, and even breaks. Due to the presence of numerous ester bonds in the fiber molecular chain, the degradation process begins with the small molecules of water moving to the surface of the polymer material and diffusing into the ester bonds or around the hydrophilic groups. The ester bonds break under acid catalysis, causing the polymer molecular weight to decrease and the regular structure of the polymer to be destroyed, which is manifested as the polymer film gradually changing from a relatively smooth surface to a rough surface with the appearance of some micropores or breaks. Fig.13 Each group showed different degrees of degradation. At 4 weeks, the degradation rate of group P2 was higher, while that of group P0 was the lowest. The *P values between the two time periods of P1 and P0 were all <0.05, which was statistically significant, indicating that the degradation rate of pure PLGA was high within the same period of time, and the time required for complete degradation may be shorter, which is similar to the results reported in the literature.
[0102] Example 3 Cell culture and proliferation
[0103] 3.1 Cell culture methods
[0104] Prior to cell culture, all samples were sterilized by UV irradiation (30 min per side) and sterilized by autoclave at 121 °C. -2 The obtained cells were cultured in complete culture medium (CM-R200 / CM-R145, Procell) at 37°C and 5% CO2 in a saturated humidity. When the cells reached 80% aggregation, 0.25% trypsin-EDTA solution was used to subculture the cells. The third generation of cell lines was used in the following experiments. In order to detect the viability and proliferation ability of cell lines on hydrogels and fiber membranes, the samples were incubated with fibronectin solution to promote cell adhesion. 5×10 4 Cells were inoculated on the samples and cultured for different time periods (1d, 3d, 5d, 7d) to promote cell proliferation. After 1 day of culture, cell viability was confirmed by live / dead assay. For cell morphology and proliferation observation, the cells on the scaffolds were fixed and incubated with phalloidin and DAPI for cytoskeleton and nucleus staining, respectively. Then, the samples were observed under a confocal laser scanning microscope.
[0105] 3.2 Cell morphology
[0106] The cells were stained with DAPI at 1d, 3d, 5d, and 7d after culture, and the cell status was observed using a laser confocal microscope (AX, Nikon, Japan).
[0107] 3.3 Cell viability
[0108] The cell culture flasks were routinely treated and counted, and inoculated in 96-well plates. A blank well was added for inoculation according to the experimental groups. Five replicate wells were set up for each group. When the cells grew to 90%, 10 μL of CCK-8 solution (1 h) was added according to the experimental groups. The OD value (Wavelength: 450 nm) was detected by Molecular Devices, Spectra MAX M5 microplate reader, and the cell viability was calculated.
[0109] Depend on Fig.14 It can be seen that the nucleus pulposus cells in each group are unevenly distributed. Fig.15 The number of cells per unit area in the ef fluorescent region was significantly lower than that in other groups, indicating that the proliferation of G5 and G0 nucleus pulposus cells was relatively small. Fig.16 The distribution of annular fiber cells in each group was uneven. Fig.15 Ae in the middle showed more blue-stained nucleoplasm, indicating that the P1-5 group had relatively more nuclei in terms of morphology and number. Fig.16 It shows that each group of hydrogels and fiber membranes can promote cell viability. Fig.16 Figure a shows the difference between G2 and G3 groups at 4 weeks *P=0.91771, indicating that although the OD values of the two groups were similar, there was no difference in cell viability. Fig.16Figure b shows the statistical difference between P4 and P5 groups at 4 weeks, **P=0.0001, which shows a significant difference, indicating that the P5 group is significantly better than the P4 group in improving cell viability.
[0110] Example 4 Animal Experiment
[0111] 4.1 Construction of tissue-engineered intervertebral disc
[0112] like Fig.17 The special circular sleeve mold shown in the figure was first used to move the mold up and down on the G3 group hydrogel matrix prepared under ultraviolet light to cut out a disc-shaped gel block with a diameter of 3mm and a height of 1.5mm to construct a tissue engineering nucleus pulposus (TE-Nucleus Pulposus, TE-NP). Then the P0 group electrospun ordered fiber membrane was cut into strips with a length of 50mm and a width of 1.5mm. The upper and lower strips were arranged at ±30° according to the fiber running direction, named Test 30 (Test 30, T30). In order to compare the effects of other different angle arrangements on stress-strain, the following three control groups were set up: parallel arrangement group (Testparallel, TP), ±45° arrangement group (Test45, T45), and random arrangement group (Test random, TR). The two adjacent strips were curled and wrapped around the outer wall of the artificial nucleus pulposus according to the arrangement direction of each group to form 8-10 layers of tissue engineering fiber ring (TE-Annulus Fibrosus, TE-AF). In order to avoid the biological toxicity caused by traditional adhesives, this research invention does not use any adhesives during the winding process. Next, a universal material testing machine is used to test the compression performance of tissue engineering intervertebral disc (TE-IVD) specimens constructed with 4 different arrangements of fiber membranes, so as to select the group with the best mechanical strength for subsequent animal experiments. The setting parameters are as follows: maximum stress 100N, pressure plate movement speed 5mm / min, and recovery to the initial position under 70% compression deformation. The experimental results are as follows: Fig.18 As shown in Figure a, within a compression test cycle, the T30, T45, and TR groups all showed complete stress-strain curves. The T45 group had a relatively high curve peak, while the T30 group had a lower curve peak, and deformation occurred under a small compressive stress. In addition, the TP group ruptured during the compression process, indicating that the TE-IVD composed of parallel arrangements was not suitable for subsequent experiments. The elastic modulus of each group is shown in Figure 2. Fig.18As shown in middle b: TP 0.90774±0.07717kPa, T30 0.71±0.05153kPa, T45 1.77863±0.13507kPa, TR 1.12052±0.096kPa. The elastic modulus of the T30 group is relatively small, indicating that under a certain stress, the TE-IVD arranged at ±30° has a greater elastic deformation.
[0113] The P1-5 groups of electrospun ordered fiber membranes were arranged at ±30° to construct TE-IVD. The compression test results are shown in Fig. 20 As shown in ae, in a compression test cycle, P3, P4, P5, P0 (i.e. Fig.18 The P3 group has a relatively high peak value, while the P5 and P0 / T30 groups have lower peak values and similar values, which can cause deformation under a small compressive stress. In addition, the P1 and P2 groups deformed and ruptured during the compression process, indicating that these two groups of TE-IVD are not suitable for implantation in animals. Fig.19 As shown in f, P1 0.27311±0.02603kPa, P2 1.16984±0.14816kPa, P3 1.80953±0.15763kPa, P4 0.9265±0.07307kPa, P5 0.84153±0.06841kPa. The stress-strain curve of the P5 group was complete, and the elastic modulus was relatively small and close to that of the P0 / T30 group, indicating that under a certain stress, the TE-IVD composed of the fiber membrane in this group had a large elastic deformation, and the P5 group was selected for animal implantation.
[0114] 4.2 Animal modeling and in vivo intervention
[0115] Twelve SD rats (male, 8 weeks old) were selected, and the experimental animal license was SLXK (Lu) 20210002. The preferred TE-IVD was implanted into the 3 / 4 caudal vertebra of the rat to evaluate its function. 3% sodium pentobarbital was used, and the dosage was 0.1-0.2 mL / 100 g. -1 In addition to the TE-IVD based on the P5 group, we also set the discectomy group as the Control group. For the TE-IVD group, the autologous nucleus pulposus and annulus fibrosus were removed and replaced with artificial implants. Fig.21 a. For the discectomy group, a section of autologous IVD was dissected without any implantation. To ensure that the implant could maintain stability between adjacent vertebrae after TE-IVD implantation, a special external fixator was used to fix the adjacent caudal vertebrae of the rat ( Fig.21 b) After the operation, intramuscular injection of cefazolin sodium 0.36 g kg within 48 hours -1 ·d-1 To fight infection.
[0116] 4.3 Imaging Detection
[0117] In order to observe the morphology immediately after surgery and 1 month after implantation, the Mouse Coil-8 type rat tail coil ( Fig. 20 c) obtained the magnetic resonance imaging (MRI) T1WI and other signal sequences of the coccygeal vertebrae, such as Fig. 20 As shown in dg; and a high-resolution MRI T2WI high-signal sequence of the coccygeal intervertebral disc was obtained (resolution: 0.5mm×0.5mm×0.5mm), as shown in Fig. 20 As shown in HK.
[0118] In order to make the MR imaging of the intervertebral disc clearer, we use a special phantom as a standard reference to improve the clarity, such as Fig. 20 The gray-white rectangular area indicated by the white arrow in the upper right corner of middle d, Fig. 20 The red arrow in dk also indicates the target segment for intervention. The imaging results show that immediately after surgery, the intervertebral disc of the control group was removed and there was varying degrees of collapse and even dislocation of the intervertebral disc ( Fig. 20 d, e), while no obvious abnormality was found in the intervertebral disc space of the TE-IVD group ( Fig. 20 f, g). 4 weeks after surgery, the intervertebral disc shortened to varying degrees in each group ( Fig. 20 Chinese (HK).
[0119] 4.4 Histological examination
[0120] Four weeks after implantation, the rats were anesthetized and killed, and the intact intervertebral tissue blocks were removed and placed in a pre-prepared paraformaldehyde tissue fixative. After decalcification of the bone tissue, dehydration and transparency, wax immersion embedding, sectioning, dewaxing and staining, dehydration and transparency, and sealing, the HE and MASSON morphologies of the intervertebral tissues of each group were observed under an inverted fluorescence microscope.
[0121] from Fig.21 It can be observed that the tissue structure of each group is clear, and HE staining shows no obvious rejection reaction, indicating good biocompatibility. The TE-IVD group and the normal IVD group both have complete intervertebral structures, including the end plate (EP), disc-shaped NP and multi-layer concentric ring AF, while the Control group only observed EP and messy interstitial tissue, without complete disc-derived structures ( Fig.21 Normal IVD group ( Fig.21 In the middle (b, e), there is an obvious white ring area between NP and AF, with a clear boundary. In the TE-IVD group, NP and AF are closely adjacent, with a blurred boundary and unclear edge ( Fig.21 (a, d) In the TE-IVD group, MASSON staining is the main method to show fibers in tissues. Fig.21 The top or bottom of the NP indicated by the arrows in d and e has no layered AF distribution in the TE-IVD group, but has a small amount of layered AF distribution in the IVD group. This is because when making TE-IVD, the fiber membrane is only curled and wrapped around the outer wall of the NP without covering the top or bottom, so as to better simulate the disc structure of the natural IVD.
[0122] in conclusion
[0123] The present invention first selects the photosensitive material GelMA with good biocompatibility and the double-bond PEGDA as the adhesive between tissues to construct the nucleus pulposus of UV-curable hydrogel. Next, electrostatic spinning is used to obtain orderly arranged micro-nano fiber rings. In order to simulate the concentric ring structure of natural fiber rings, the micro-nano fiber rings are arranged in different orientations, and a new electrostatic spinning process with strong mechanical properties is optimized. The polymer material PLGA / PCL is compounded with the natural material type I collagen to prepare a fiber ring with high simulation of the inner and outer layers. The characterization, mechanical properties, cell differentiation and other conditions of the tissue-engineered nucleus pulposus and fiber ring were tested respectively. Finally, the tissue-engineered intervertebral disc was integratedly constructed by the self-assembly method, and the effect of this material on repairing intervertebral disc degeneration in vivo was observed in an animal model, which provides a new strategy for the clinical treatment of the disease.
[0124] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A tissue engineered intervertebral disc, characterized in that: It is composed of the nucleus pulposus and the annulus fibrosus.
2. The tissue engineered intervertebral disc according to claim 1, characterized in that: The nucleus pulposus components include GelMA, PEGDA, a photoinitiator and L-cysteine; the photoinitiator is I-2959 or LAP.
3. The tissue engineered intervertebral disc according to claim 2, characterized in that: The mass ratio of the GelMA, PEGDA, photoinitiator and L-cysteine is 1-2:1-2:0.5:0-1.
4. The tissue engineered intervertebral disc according to claim 1, characterized in that: The annulus fibrosus components include poly (D, L-lactic-co-glycolic acid), polycaprolactone and type I collagen.
5. The tissue engineered intervertebral disc according to claim 4, characterized in that: The fiber ring is composed of poly (D, L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen in a mass ratio of 0-10:0-10:0-1.
6. The method for preparing a tissue-engineered intervertebral disc according to claim 1, characterized in that: The nucleus pulposus is made by ultraviolet light curing, and the fiber ring is made by electrostatic spinning.
7. The preparation method according to claim 6, characterized in that: The ultraviolet curing is to prepare GelMA, PEGDA and I-2959 into an aqueous solution in a mass percentage of 1-2:1-2:0.5, and irradiate under a 365nm LED UV curing lamp for 2 hours.
8. The preparation method according to claim 6, characterized in that: The electrospinning method comprises: preparing a precursor HFIP spinning solution by mixing poly (D, L-lactic acid-co-glycolic acid), polycaprolactone and type I collagen in a mass percentage of 0-10:0-10:0-1, and spinning using a portable electrospinning apparatus.
9. Use of the tissue engineered intervertebral disc as claimed in any one of claims 1 to 5 in the preparation of a product for repairing intervertebral disc degeneration and reducing the loss of intervertebral disc signal intensity.
